Radionuclide applicator and preparation method thereof
By extracting and preparing a high-purity SrCO3-Ag active layer from the radioactive waste liquid, combined with the source core of a multi-layer sealed structure, the problem of difficulty in effectively using the radioactive waste liquid in the prior art is solved, and a radionuclide applicator with high safety and uniformity is achieved.
Patent Information
- Application Number
- CN202411573905.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-04
AI Technical Summary
Existing radionuclide applicators are difficult to effectively utilize the high-calorie nuclides in radioactive waste liquid, and the preparation process is complex, making safety and uniformity difficult to ensure.
Through the steps of extraction, back-extraction, precipitation, calcination, pressing, and rolling from the radioactive waste liquid, an SrCO3-Ag active layer with high purity and high uniformity is prepared, and combined with a source core of a multi-layer sealing structure, a radionuclide applicator with excellent sealing performance is formed.
The effective utilization of high-calorie nuclides in radioactive waste liquid is achieved, the danger of radioactive waste liquid is reduced, the safety and radiation uniformity of the applicator are improved, and the process is relatively simplified and the operation is relatively simple.
Smart Images

Figure CN119548771A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of applicators, and in particular to a radionuclide applicator and a preparation method thereof. Background Art
[0002] Radionuclide applicators are radionuclides of a certain activity and energy that are sealed in a certain way to serve as a radiation source for patch therapy, thereby treating superficial skin lesions. Regarding the research on radionuclide applicators, some finished products have been produced and sold abroad, and have been used in hospitals to treat tumors, scars, and skin diseases.
[0003] In recent years, with the development of separation and purification technology of strontium-90 and yttrium-90 in domestic radioactive waste liquid, the purity of strontium-90 and yttrium-90 products has gradually met the requirements for application in medical applicators. Therefore, a process for preparing applicators using radioactive waste liquid is proposed to utilize the radioactive nuclides in the radioactive waste liquid. Summary of the invention
[0004] The purpose of the present invention is to provide a radionuclide applicator, the radioactive material used in the radionuclide applicator is derived from radioactive waste liquid, and can reduce the high heat release nuclides in the radioactive waste liquid. The second purpose of the present invention is to provide a preparation method of the radionuclide applicator.
[0005] The present invention provides a radionuclide applicator, comprising a shell, a handle being provided on the shell, a source core being provided inside the shell, the source core comprising, from the inside to the outside, a first palladium layer, a first silver layer, an active layer, a second silver layer, and a second palladium layer, wherein the active layer is a SrCO3-Ag layer; epoxy resin layers are provided around the source core and on the side wall close to the handle;
[0006] The thickness of the first palladium layer is 0.02-1 μm, the thickness of the first silver layer is 0.05-2.0 mm; the thickness of the active layer is 0.01-0.1 mm, the thickness of the second silver layer is 0.005-0.2 mm, the thickness of the second palladium layer is 0.02-1 μm; the thickness of the epoxy resin layer is 0.05-5 mm.
[0007] Furthermore, the shell is made of aluminum or stainless steel, the thickness of the shell is 0.05-2 mm, and the handle is made of organic glass or stainless steel.
[0008] The present invention provides a method for preparing the above-mentioned radionuclide applicator, comprising the following steps:
[0009] S1. Extraction: Use radioactive waste liquid and 0.1 mol / L crown ether-n-octanol as extractant to perform multi-stage countercurrent extraction in a centrifugal extractor. 90Sr is extracted into the organic phase, the residual aqueous phase is discarded, and the residual organic phase enters the stripping system;
[0010] S2. Stripping: Strip the above-mentioned organic phase with 1.0 mol / L nitric acid solution. 90 Sr is extracted from the organic phase into the aqueous phase to obtain a stripping solution;
[0011] S3. Standing: Transfer the stripping solution to a shielding tank and let it stand for growth. 90 Y, and the product liquid was obtained, the radioactivity in the product liquid reached 7.4×10 10 Bq / L;
[0012] S4. Coprecipitation: 2 mol / L silver nitrate solution and 0.5 mol / L strontium nitrate solution were added to the above product solution, stirred evenly, and 0.5 mol / L oxalic acid was added, and the pH was adjusted to 5.8-6.2 with ammonia water. The mixed solution was precipitated and filtered to obtain a coprecipitated sample;
[0013] S5 Calcination: Sequentially use deionized water, alcohol to wash the coprecipitated sample, after washing the coprecipitated sample was dried, the dried sample was calcined at 190-210 ℃ for 9.5-10.5 hours to obtain an active powder;
[0014] S6. Compression: Take the active powder and press it with a tablet press to obtain an active chip; take the silver powder and press it with a tablet press to obtain a first silver sheet and a second silver sheet; place the first silver sheet and the second silver sheet on both sides of the active chip and press them to obtain a pellet;
[0015] S7. Sintering: The pressed pellets are placed in a muffle furnace for sintering at a sintering heating rate of 10°C / min, a sintering temperature of 745-755°C, a sintering constant temperature time of 28-32min, and the sintered pellets are naturally cooled to room temperature;
[0016] S8. Cold rolling: The core block cooled to room temperature is cold rolled on a tablet press;
[0017] S9. Hot rolling: The cold-rolled core block is heated in a muffle furnace, annealed after heating, and then placed in a heated tablet press for hot rolling to obtain a source sheet;
[0018] S10. Decontamination: Decontaminate the surface of the source wafer to ensure that the contamination on the surface of the source wafer is below 200 Bq;
[0019] S11. Radiation uniformity measurement: The decontaminated source sheet is subjected to source surface uniformity measurement, and the measured radiation uniformity deviation is no more than ±5%;
[0020] S12. Electroplating pretreatment: The qualified source sheet is subjected to electroplating pretreatment, using 0.1 mol / L sodium hydroxide solution for alkali treatment, washing with deionized water and then acid treatment with 0.1 mol / L hydrochloric acid solution, and then washing with deionized water and alcohol, and drying;
[0021] S13. Electroplating: Electroplating the pre-treated source sheet, with the source sheet as the cathode and the palladium sheet as the anode. After the electroplating is completed, the sample is cleaned with deionized water and alcohol, and finally dried;
[0022] S14. Punching: Use a punching machine to punch the electroplated sample to obtain the required size;
[0023] S15. Gluing: The source sheet cut to size is sealed with epoxy resin crystal glue to obtain a source core;
[0024] S16. Assembling: Assemble the source core and the shell, and finally assemble the handle and the shell to obtain the applicator product.
[0025] Preferably, in step S1, the rotation speed of the centrifugal extractor is 3400-3600 rpm, a plunger pump is used for sampling, the organic phase sampling speed is 200 mL / h, and the extraction agent sampling speed is 100 mL / h; in step S2, the stripping is performed by a centrifugal extractor with a rotation speed of 2900-3100 rpm, a plunger pump is used for sampling the stripping solution, and the stripping agent sampling speed is 120 mL / h.
[0026] Preferably, the specific operation of step S4 is as follows: take 0.1L of product liquid in a beaker, add 0.2L of 2mol / L silver nitrate solution and 0.01L of 0.5mol / L strontium nitrate solution to the product liquid, stir evenly, add 0.5L of 0.5mol / L oxalic acid, use ammonia water to adjust the pH value to 5.8-6.2, precipitate, filter with slow filter paper after precipitation, and obtain a co-precipitated sample.
[0027] Preferably, the specific operation of step S6 is as follows: the pressing pressure of the active chip is 20KN, and the constant pressure time is 5 minutes; the mesh size of the silver powder used is 500 mesh, and the pressing pressure of the first silver sheet and the second silver sheet is 20KN; the pressing pressure of the first silver sheet, the second silver sheet and the active chip is 30KN.
[0028] Preferably, the specific operation of step S8 is as follows: rolling the core block cooled to room temperature on a roller tablet press, the rolling speed of the roller tablet press is 2.00 cm / min, the rolling thickness decreases to 0.025 cm, and the number of rolling times is 4.
[0029] Preferably, the specific operation of step S9 is as follows: placing the cold-rolled core block in a muffle furnace for heating at a temperature of 680-720° C. for a constant temperature heating time of 18-22 min, annealing for 5-6 min, placing the annealed core block in a roller sheet press heated to 83-87° C. for hot rolling at a rolling speed of 2 cm / min; the rolling thickness is reduced by 0.020 cm each time, the rolling number is 5, and a source sheet is obtained.
[0030] Preferably, the electroplating solution used in step S12 comprises 10 g / L palladium chloride, 10 g / L boric acid, 150 g / L ammonium chloride, and 4 g / L pyridine-2-carboxylic acid, the electroplating temperature is 48-52°C, and the electroplating current is 8 A / dm 2 , the electroplating time is 5-7s.
[0031] Preferably, the method further comprises the following steps:
[0032] S17. Determination: The applicator product obtained in step S16 is tested for leakage rate using a wiping method, a uniformity test using a black meter, and an air absorption dose rate test on the source surface of the applicator using an activity meter;
[0033] S18. Laser marking: Laser marking is performed on the qualified applicators to ensure that each source core has a specific code;
[0034] S19. Storage: Transfer the marked applicator to a shielded container for storage.
[0035] In summary, compared with the prior art, the present invention has the following advantages:
[0036] The radionuclide applicator provided by the present invention combines and coats the first palladium layer, the first silver layer, the second silver layer, the second palladium layer and the active layer to obtain a radioactive source core with excellent sealing performance, high safety, light structure and simple operation. The radioactive material of the active layer used in the radionuclide applicator provided by the present invention is extracted from radioactive waste liquid, obtained after separation and purification, and has the characteristics of high purity, reducing the nuclides with high heat release in the radioactive waste liquid, and the active layer is obtained by precipitation, filtration, calcination, pressing and rolling, and has high uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 Schematic diagram of the structure of the radionuclide applicator in an embodiment of the present invention;
[0039] Figure 2 It is a process flow chart in an embodiment of the present invention.
[0040] Explanation of the reference numerals: 1 - housing; 2 - handle; 3 - epoxy resin layer; 4 - first palladium layer, 5 - first silver layer; 6 - active layer; 7 - second silver layer; 8 - second palladium layer. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0043] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0044] Example
[0045] A radionuclide applicator, such as Figure 1 As shown, it includes a shell 1 and a handle 2, and an active core is arranged inside the shell 1.
[0046] The shell 1 and the handle 2 are the shells and handles in the prior art, and the connection between the shell 1 and the handle 2 is a snap connection. The shell 1 is made of aluminum or stainless steel with a thickness of 0.05-2 mm. The handle 2 has a diameter of 1.0 cm and a length of 12 cm, and is made of organic glass or stainless steel.
[0047] The source core is a multi-layer sealed structure with a radioactivity of 20-40mCi. Epoxy resin layers 3 are provided on the four sides and the top wall of the source core, and the source core includes a first palladium layer 4, a first silver layer 5, an active layer 6, a second silver layer 7, and a second palladium layer 8 from top to bottom. The active layer 6 is a SrCO3-Ag layer. The thickness of the epoxy resin layer 3 is 0.05-5mm; the thickness of the first palladium layer 4 is 0.02-1μm, the thickness of the first silver layer 5 is 0.05-2.0mm; the thickness of the active layer 6 is 0.01-0.1mm, the thickness of the second silver layer 7 is 0.005-0.2mm, and the thickness of the second palladium layer 8 is 0.02-1μm.
[0048] The preparation method of the above-mentioned applicator is as follows Figure 2 As shown, the details are as follows:
[0049] S1. Extraction: Use radioactive waste liquid and 0.1 mol / L crown ether-n-octanol as extractant to perform 10-stage countercurrent extraction in a centrifugal extractor. 90 Sr is extracted into the organic phase, and most of the other impurities such as 137 Cs, 241 Am etc. remain in the aqueous phase, the residual aqueous phase is discarded, and the residual organic phase enters the stripping system; the centrifugal extractor is driven by a motor, the size is Φ20mm, the speed is 3500rpm, the plunger pump is used for sampling, the organic phase sampling speed is 200mL / h, and the extraction agent sampling speed is 100mL / h; the crown ether in the extractant of this embodiment is dicyclohexyl-18-crown-6 (DCH 18 C6).
[0050] S2. Stripping: The above-mentioned residual organic phase was stripped by washing with 1.0 mol / L nitric acid solution for 2 levels. 90 Sr is extracted from the organic phase into the aqueous phase to obtain a stripping solution; the stripping is performed using a centrifugal extractor, which is driven by a motor, has a size of Φ20mm, and a rotation speed of 3000rpm. A plunger pump is used to inject the stripping solution, and the stripping agent injection speed is 120mL / h.
[0051] S3. Standing: Transfer the stripping solution to a shielding tank and let it stand for 2 months. 90 Y, and the product liquid was obtained. After the strontium and yttrium in the product liquid reached radioactive equilibrium, the radioactivity was measured. The radioactivity in the product liquid reached 7.4×10 10 Bq / L.
[0052] S4. Co-precipitation: Take 0.1L of the product liquid in a beaker, add 0.2L of 2mol / L silver nitrate solution and 0.01L of 0.5mol / L strontium nitrate solution to the product liquid, stir evenly, add 0.5L of 0.5mol / L oxalic acid, adjust the pH value to 6 with ammonia water, precipitate the mixed solution, and filter with a slow filter paper with a diameter of 15 cm after precipitation to obtain a co-precipitated sample.
[0053] S5. Calcination: Wash the co-precipitated sample three times with deionized water and then three times with alcohol, then place the co-precipitated sample in an oven at 90°C for drying. Transfer the dried sample to a crucible and place it in a muffle furnace and calcine it at 200°C for 10 hours to obtain an active powder.
[0054] S6. Compression: Weigh 2.5g of active powder and use a tablet press to compress the powder. The size of the compressed active chip is: 3.00cm×2.00cm×0.05cm, the pressing pressure is 20KN, and the constant pressure time is 5 minutes; use silver powder with a mesh size of 500 to compress the first silver sheet and the second silver sheet. Weigh 15g of silver powder to compress the first silver sheet. The size of the first silver sheet is 3.20cm×2.20cm×0.30cm, and the pressing pressure is 20KN; weigh 5g of silver powder to compress the second silver sheet. The size of the second silver sheet is 3.20cm×2.20cm×0.10cm, and the pressing pressure is 20KN; the first silver sheet, the active chip, and the second silver sheet are compressed in three-in-one, the pressing pressure is 30KN, and the size of the compressed core block is 3.20cm×2.20cm×0.40cm.
[0055] S7. Sintering: The pressed pellets are placed in a muffle furnace for sintering at a sintering heating rate of 10°C / min, a sintering temperature of 750°C, and a sintering constant temperature time of 30min. The sintered pellets are naturally cooled to room temperature.
[0056] S8. Cold rolling: The core blocks cooled to room temperature are rolled on a roller sheet press at a rolling speed of 2.00 cm / min; the rolling thickness is gradually reduced to 0.025 cm, the number of rolling times is 4, and the target final thickness of the cold rolling is 0.30 cm.
[0057] S9. Hot rolling: Place the cold-rolled core blocks in a muffle furnace for heating at 700°C, keep the heating constant for 20 minutes, and anneal for 5 minutes. Place the annealed core blocks in a roller sheet press heated to 85°C for hot rolling at a rolling speed of 2 cm / min. The rolling thickness decreases by 0.020 cm each time, the number of rolling times is 5, and the final rolling target thickness is 0.20 cm to obtain the source sheet.
[0058] S10. Decontamination: Use an ultrasonic cleaner and cotton balls to clean the surface of the source wafer to ensure that the contamination on the surface of the source wafer is below 200 Bq.
[0059] S11. Radiation uniformity measurement: The decontaminated source sheet is shipped to the monitoring room, photographed using a densitometer and film, and the source surface uniformity is measured at multiple points. The radiation uniformity deviation of the multi-point densitometer value measurement is no more than ±5%.
[0060] S12. Pre-treatment for electroplating: The qualified source sheets are subjected to pre-treatment for electroplating by using 0.1 mol / L sodium hydroxide solution for alkali treatment twice, washing with deionized water twice, and then using 0.1 mol / L hydrochloric acid solution for acid treatment twice, and then washing with deionized water twice, and finally washing with alcohol twice, and drying with an infrared lamp.
[0061] S13. Electroplating: Electroplating the processed source sheet, with the source sheet as the cathode and the palladium sheet as the anode; the composition of the electroplating solution is 10g / L palladium chloride, 10g / L boric acid, 150g / L ammonium chloride, and 4g / L pyridine-2-carboxylic acid; the electroplating temperature is controlled at 50°C, and the electroplating current is 8A / dm 2 The electroplating time was 5s. The electroplated samples were washed twice with deionized water and twice with alcohol, and finally dried with an infrared lamp.
[0062] S14. Punching: Use a punching machine to punch out the source sheet after electroplating. According to the design of the applicator, use different punching dies to punch out the samples after electroplating and cleaning. Common shapes include squares with sizes of 3.0cm×2.0cm, 3.0cm×3.0cm, 4.0cm×3.0cm, and circles with sizes of Φ3.0cm, Φ2.5cm, etc.
[0063] S15. Gluing: Use epoxy resin crystal glue to seal the source sheet after the punching out. The epoxy resin crystal glue is a commercially available product, including glue A and glue B. The ratio of glue A to glue B is 3:1. The curing time is 24 hours. The thickness of the sealing glue around the source sheet is 0.20cm, and the thickness of the glue on the top of the source sheet is 0.40cm. The source core is obtained. The thickness of the first palladium layer of the source core is 0.5μm, and the thickness of the first silver layer is 1.5mm; the thickness of the active layer is 0.1mm, the thickness of the second silver layer is 0.2mm, and the thickness of the second palladium layer is 0.5μm; the thickness of the epoxy resin layer on the top is 3.5mm.
[0064] S16. Assembly: Use conventional technical means in the art to assemble the source core and the shell, and finally assemble the handle and the shell to obtain an applicator product.
[0065] S17. Determination: The applicator product obtained in step S16 is subjected to leakage rate detection using the wiping method (leakage rate ≤ 40Bq), uniformity detection using a black meter (uniformity deviation is within ±3%), and air absorption dose rate detection on the source surface of the applicator using an activity meter (source surface dose rate 47.4±4.7mSv / h, dose rate 4.0-6.0mSv / h at a distance of 0.5 meters from the source surface); the effective activity is 20±2mCi.
[0066] S18. Laser marking: Laser marking is performed on the qualified applicators to ensure that each source core has a specific code.
[0067] S19. Storage: Transfer the marked applicator to a shielded container for storage.
[0068] The number and models of the main equipment used in the above method are shown in Table 1, and the materials and specifications used are shown in Table 2.
[0069] Table 1 List of main experimental equipment
[0070]
[0071]
[0072] Table 2 List of main experimental materials
[0073] Material Name Specification Purity Radioactive liquid waste / Strontium nitrate GR Silver nitrate GR oxalic acid GR Silver powder 500 mesh, 99.9% ammonia 25%-28% Palladium plating solution Self-preparation Epoxy Resin Crystal Epoxy AB glue
[0074] The radionuclide applicator provided by the present invention meets the following technical requirements:
[0075] (1) The surface integrity test of the applicator source window and the radioactive material leakage test meet the wiping method of "GB4076 General Regulations for Sealed Radioactive Sources" -200Bq or less;
[0076] (2) The radiation uniformity of the applicator source surface is tested by the film self-development method, and the radiation uniformity deviation is measured by a 5-point measurement with a black scale and is no more than ±5%;
[0077] (3) The air absorbed dose rate at the source surface of the applicator or the air absorbed dose rate at the reference point is measured using an activity meter and the relative measurement method. The total uncertainty of the absorbed dose rate does not exceed ±5%;
[0078] (4) The effective activity of the applicator is 20±2mCi.
[0079] The raw materials used in the applicator provided by the present invention are extracted from radioactive waste liquid, obtained through separation and purification, and have high purity characteristics; the active layer is obtained through precipitation, filtration, calcination, pressing, and rolling, and has highly uniform characteristics; the applicator is light as a whole, tightly sealed, and has a high degree of safety.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A radionuclide applicator, comprising a shell, wherein the shell is provided with a handle, characterized in that: A source core is provided inside the shell, and the source core includes a first palladium layer, a first silver layer, an active layer, a second silver layer, and a second palladium layer from the inside to the outside, and the active layer is a SrCO3-Ag layer; epoxy resin layers are provided around the source core and on the side wall close to the handle; The thickness of the first palladium layer is 0.02-1 μm, the thickness of the first silver layer is 0.05-2.0 mm; the thickness of the active layer is 0.01-0.1 mm, the thickness of the second silver layer is 0.005-0.2 mm, the thickness of the second palladium layer is 0.02-1 μm; the thickness of the epoxy resin layer is 0.05-5 mm.
2. The radionuclide applicator according to claim 1, characterized in that: The shell is made of aluminum or stainless steel, the thickness of the shell is 0.05-2 mm, and the handle is made of organic glass or stainless steel.
3. A method for preparing the radionuclide applicator according to claim 1 or 2, characterized in that: The following steps are involved: S1. Extraction: Use radioactive waste liquid and 0.1 mol / L crown ether-n-octanol as extractant to perform multi-stage countercurrent extraction in a centrifugal extractor. 90 Sr is extracted into the organic phase, the residual aqueous phase is discarded, and the residual organic phase enters the stripping system; S2. Stripping: Strip the above-mentioned organic phase with 1.0 mol / L nitric acid solution. 90 Sr is extracted from the organic phase into the aqueous phase to obtain a stripping solution; S3. Standing: Transfer the stripping solution to a shielding tank and let it stand for growth. 90 Y, and the product liquid was obtained, the radioactivity in the product liquid reached 7.4×10 10 Bq / L; S4. Coprecipitation: 2 mol / L silver nitrate solution and 0.5 mol / L strontium nitrate solution were added to the above product solution, stirred evenly, and 0.5 mol / L oxalic acid was added, and the pH was adjusted to 5.8-6.2 with ammonia water. The mixed solution was precipitated and filtered to obtain a coprecipitated sample; S5 Calcination: Sequentially use deionized water, alcohol to wash the coprecipitated sample, after washing the coprecipitated sample was dried, the dried sample was calcined at 190-210 ℃ for 9.5-10.5 hours to obtain an active powder; S6. Compression: Take the active powder and press it with a tablet press to obtain an active chip; take the silver powder and press it with a tablet press to obtain a first silver sheet and a second silver sheet; place the first silver sheet and the second silver sheet on both sides of the active chip and press them to obtain a pellet; S7. Sintering: The pressed pellets are placed in a muffle furnace for sintering at a sintering heating rate of 10°C / min, a sintering temperature of 745-755°C, a sintering constant temperature time of 28-32min, and the sintered pellets are naturally cooled to room temperature; S8. Cold rolling: The core block cooled to room temperature is cold rolled on a tablet press; S9. Hot rolling: The cold-rolled core block is heated in a muffle furnace, annealed after heating, and then placed in a heated tablet press for hot rolling to obtain a source sheet; S10. Decontamination: Decontaminate the surface of the source wafer to ensure that the contamination on the surface of the source wafer is below 200 Bq; S11. Radiation uniformity measurement: The decontaminated source sheet is subjected to source surface uniformity measurement, and the measured radiation uniformity deviation is no more than ±5%; S12. Electroplating pretreatment: The qualified source sheet is subjected to electroplating pretreatment, using 0.1 mol / L sodium hydroxide solution for alkali treatment, washing with deionized water and then acid treatment with 0.1 mol / L hydrochloric acid solution, and then washing with deionized water and alcohol, and drying; S13. Electroplating: Electroplating the pre-treated source sheet, with the source sheet as the cathode and the palladium sheet as the anode. After the electroplating is completed, the source sheet is cleaned with deionized water and alcohol, and finally dried; S14. Punching: Use a punching machine to punch the electroplated source sheet to obtain the required size; S15. Gluing: The source sheet cut to size is sealed with epoxy resin crystal glue to obtain a source core; S16. Assembling: Assemble the source core and the shell, and finally assemble the handle and the shell to obtain the applicator product.
4. The preparation method according to claim 3, characterized in that: In step S1, the rotation speed of the centrifugal extractor is 3400-3600 rpm, the plunger pump is used for sampling, the organic phase sampling speed is 200 mL / h, and the extraction agent sampling speed is 100 mL / h; In step S2, the stripping is performed by a centrifugal extractor with a rotation speed of 2900-3100 rpm, and a plunger pump is used to inject the stripping solution. The stripping agent injection speed is 120 mL / h.
5. The preparation method according to claim 3, characterized in that: The specific operation of step S4 is as follows: take 0.1L of the product liquid in a beaker, add 0.2L of 2mol / L silver nitrate solution and 0.01L of 0.5mol / L strontium nitrate solution to the product liquid, stir evenly, add 0.5L of 0.5mol / L oxalic acid, use ammonia water to adjust the pH value to 5.8-6.2, precipitate, filter with slow filter paper after precipitation, and obtain a co-precipitated sample.
6. The preparation method according to claim 3, characterized in that: The specific operation of step S6 is as follows: the pressing pressure of the active chip is 20KN, and the constant pressure time is 5 minutes; the mesh size of the silver powder used is 500 mesh, and the pressing pressure of the first silver sheet and the second silver sheet is 20KN; the pressing pressure of the first silver sheet, the second silver sheet and the active chip is 30KN.
7. The preparation method according to claim 3, characterized in that: The specific operation of step S8 is as follows: rolling the core block cooled to room temperature on a roller tablet press, the rolling speed of the roller tablet press is 2.00 cm / min, the rolling thickness decreases to 0.025 cm, and the number of rolling times is 4.
8. The preparation method according to claim 3, characterized in that: The specific operation of step S9 is as follows: placing the cold-rolled core block in a muffle furnace for heating at a temperature of 680-720° C. for a constant temperature heating time of 18-22 min, annealing for 5-6 min, placing the annealed core block in a roller sheet press heated to 83-87° C. for hot rolling at a rolling speed of 2 cm / min; the rolling thickness is reduced by 0.020 cm each time, the rolling number is 5, and a source sheet is obtained.
9. The preparation method according to claim 3, characterized in that: The electroplating solution used in step S12 includes 10 g / L palladium chloride, 10 g / L boric acid, 150 g / L ammonium chloride, and 4 g / L pyridine-2-carboxylic acid. The electroplating temperature is 48-52° C., and the electroplating current is 8 A / dm 2 , the electroplating time is 5-7s.
10. The preparation method according to claim 3, characterized in that: The following steps are also included: S17. Determination: The applicator product obtained in step S16 is tested for leakage rate using a wiping method, a uniformity test using a black meter, and an air absorption dose rate test on the source surface of the applicator using an activity meter; S18. Laser marking: Laser marking is performed on the qualified applicators to ensure that each source core has a specific code; S19. Storage: Transfer the marked applicator to a shielded container for storage.
Citation Information
Cited By
Strontium yttrium applicator source core and preparation method thereof
CN121081855A
Medical strontium applicator source core and preparation method thereof
CN121102767A